The Emerging Role of Hepatocellular eNOS in Non-alcoholic Fatty Liver Disease Development - Cunningham, Rory P.; Sheldon, Ryan D.; Rector, R. Scott (Frontiers in Physiology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is comprised of a spectrum of liver injury ranging from excess fat accumulation in the liver (steatosis), to steatohepatitis (NASH), to its end stage of cirrhosis. A hallmark of NAFLD progression is the decline in function of hepatic mitochondria, although the mechanisms remain unresolved. Given the important role endothelial nitric oxide synthase (eNOS) plays in mitochondrial dynamics in other tissues, it has emerged as a potential mediator of maintaining mitochondrial function in the liver. In this mini review, we summarize the most relevant findings that extends current understanding of eNOS as a regulator of mitochondrial biogenesis, and identifies a potential additional role in mitochondrial turnover and attenuating inflammation during NAFLD development and progression.